An examination of attentional control on posttraumatic stress symptoms and problematic alcohol use. (1st July 2020) - Preston, Thomas J.; Raudales, Alexa M.; Albanese, Brian J.; Schmidt, Norman B.
Highlights: Attentional control mediated trauma symptoms and alcohol use. Trauma symptoms did not mediate attentional control and alcohol use. This specificity informs trauma-related interventions aiming to reduce alcohol use. Results were derived from cross-sectional data; causal inference cannot be determined. Abstract: Trauma-exposed individuals, specifically those with higher posttraumatic stress symptoms (PTSS), are at elevated risk of developing alcohol-related problems. One mechanism via which PTSS may contribute to problematic alcohol use is poor attentional control (AC). AC theory suggests that increases in PTSD-related distress will reduce AC, which could then yield greater problematic alcohol use. An alternative path suggests poor AC amplifies PTSS, thereby promoting alcohol abuse. To date, no research has simultaneously evaluated these two pathways. Trauma exposed participants ( N  = 339) completed self-report measures on trauma related symptoms, AC, and alcohol use. Cross-sectional analyses tested direct effects of PTSS and AC on problematic alcohol use as well as indirect effects of PTSS on alcohol use via AC and AC on alcohol use via PTSS. Results revealed AC mediated the relationship between PTSS and problematic alcohol use, however PTSS did not mediate the relationship between AC and alcohol use. Current results demonstrate specificity for AC as a mediator in the relationship between PTSS and alcohol use. Future work is needed to determine if the observed statistical mediation effects extend to inform causal models of posttraumatic stress disorder (PTSD) and AUD comorbidity, and if intervening on AC mitigate PTSD and AUD symptomology.